Serum separator tube method for matrix-assisted laser desorption/ionization time-of-flight analysis - Freimann, Sarit (Access Microbiol, 2019)
BACKGROUND: Without appropriate treatment, bloodstream infections have a high mortality rate. Quicker identification of the microbial pathogen allows the clinician to develop an initial strategy of antimicrobial therapy. Sample preparation protocols for matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-ToF MS; Bruker Daltonics for Microflex LT spectrometer) technology were evaluated in an attempt to identify pathogens directly from positive blood culture bottles and thus shorten the time to identify them. This application requires preparatory processing because blood culture bottles contain undesirable proteins. This study aimed to evaluate two methods for microbial preparation for identification by MALDI-ToF MS. METHODS: This study evaluated two methods for microbial preparation from 200 positive blood culture samples, half prepared by the differential centrifugation method and half with the serum separator tube method for identification by MALDI-ToF MS. Both methods were compared to conventional methods such as VITEK II and ChromAgar culture plates. RESULTS: All Gram-negative bacteria tested were identified correctly by MALDI-ToF MS compared to conventional methods, regardless of the preparation method. However, more Gram-positive bacteria were identified when the serum separator tube method was used (83.3%) compared with the differential centrifugation method (65.3  %). Moreover, the serum separator tube protocol requires 12–15 min, while the differential centrifugation protocol requires 30–45 min. CONCLUSIONS: Sample preparation using the serum separator tube method is easy to perform, fast and reliable for accurate microbial identification by MALDI-ToF MS technology.